Portable meters for nutritional assessment in plants of gerbera fertigated with electrical conductivity levels - Mota, Poliana R. D'a.; Villas Bôas, Roberto L. [UNESP]; Ludwig, Fernanda; Fernandes, Dirceu M. [UNESP]; Folegatti, Marcos V. (Departamento de Engenharia Agrícola - UFCG, 2014)
Rapid tests to assess the nutritional status of plants gerbera can make easier the decision of any adjustments in the fertilization of the substrate. The study was conducted to evaluate nutritionally fertigated gerbera plants with increasing levels of electrical conductivity (EC), using portable meters nitrate and potassium, and chlorophyll. For this, two experiments were conducted. A randomized block design with five levels of EC (0.5, 2.0, 3.5, 5.0 and 6.5 dS m-1) and four replications was used. Cherry cultivar was used in the first experiment. In the second experiment, two cultivars (Cherry and Salmon Rose) were used. In the first experiment, the sap of the leaves was subjected to rapid testing of N-NO3- (equipment Cardy Horiba C -141). N-NO3- and K+ (C-131) were determined in the substrate solution. The intensity of the green leaf, in the second experiment was evaluated with portable Chlorophyll Meter. The N content in the indicator leaf in the first and N and K contents in the plant in the second experiment were determined. Rapid tests are presented as good indicators of the level of N-NO3- and K+ in plant tissue, with the advantages of convenience and speed of determination, facilitating monitoring of fertilization of the substrate by producers and technicians.

Os testes rápidos para avaliação do estado nutricional de plantas de gérbera podem tornar mais fácil a decisão de eventuais ajustes na fertilização do substrato. O estudo foi conduzido com o objetivo de se avaliar, nutricionalmente, plantas de gérbera fertirrigadas com níveis crescentes de condutividade elétrica (CE), utilizando-se medidores portáteis de nitrato e potássio, além de clorofilômetro. Para isto foram realizados dois experimentos. Utilizou-se um delineamento em blocos casualizados com cinco níveis de CE (0,5; 2,0; 3,5; 5,0 e 6,5 dS m-1) e quatro repetições. A cultivar Cherry foi utilizada no primeiro experimento e no segundo, duas cultivares (Cherry e Salmon Rose). No primeiro experimento a seiva das folhas foi submetida ao teste rápido de N-NO3- (equipamento Cardy Horiba C-141). Determinaram-se N-NO3- e K+ (C-131) na solução do substrato. Avaliou-se a intensidade da cor verde da folha no segundo experimento, com medidor portátil Chlorophyll Meter. Determinou-se o teor de N na folha diagnóstico no primeiro e no segundo experimento N e K da planta. Os testes rápidos se apresentam como bons indicadores do teor de N-NO3- e K+ no tecido vegetal tendo como vantagens a praticidade e a velocidade de determinação facilitando o monitoramento da fertilização do substrato por produtores e técnicos.
Medidores portáteis para avaliação nutricional em plantas de gérbera fertirrigada com níveis de condutividade elétrica
Keywords: Gerbera jamesonii L.; clorofila; seiva da folha; solução do substrato; Gerbera jamesonii L.; chlorophyll; leaf sap; solution of the substrate